Pengaruh Relationship Marketing terhadap Loyalitas Pelanggan pada Nasabah Bank BTPN KCP Sepanjang - Giina Herdian; Widyastuti Widyastuti (Universitas Negeri Surabaya, 2018)
Relationship marketing is a process of creating, maintaining and improving the strength of the value-laden relationships with customers and other stakeholders. In relationship marketing strategy there are several variables that can increase customer loyalty to the company. Among them are trust, commitment, communication and conflict resolution. This study aimed to examine the effect of relationship marketing on customer loyalty either partially or simultaneously. The sampling method used accidental sampling. Customer BTPN KCP Sepanjang the population, so the number of samples obtained by 110 customers. Methods of data analysis using multiple linear regression with SPSS software assisted. Results of the analysis in this study shows that there is significant relationship between the variables of trust, commitment, communication and conflict resolution to customer loyalty either partially or simultaneously